If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 7 = 14X + 7 + -7 Reorder the terms: 7 + X = 14X + 7 + -7 Reorder the terms: 7 + X = 7 + -7 + 14X Combine like terms: 7 + -7 = 0 7 + X = 0 + 14X 7 + X = 14X Solving 7 + X = 14X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-14X' to each side of the equation. 7 + X + -14X = 14X + -14X Combine like terms: X + -14X = -13X 7 + -13X = 14X + -14X Combine like terms: 14X + -14X = 0 7 + -13X = 0 Add '-7' to each side of the equation. 7 + -7 + -13X = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -13X = 0 + -7 -13X = 0 + -7 Combine like terms: 0 + -7 = -7 -13X = -7 Divide each side by '-13'. X = 0.5384615385 Simplifying X = 0.5384615385
| 145-342=2 | | 6x+7-7x=3 | | -10x=-4+2x | | 8=2(2c-5)c | | 13z+9=8-3z+2 | | 2x=(1/50) | | 12q=6 | | 6v^2-100=10v | | 3ln(2x+8)=14 | | 10p-7+2-1=3+5 | | 1/11 | | 2/7=x/100 | | 40x-9=71 | | 3t+10=4t+5 | | -7y+7-6=-14y+6-4 | | (-8.946)(14.08)= | | 5x+8=41 | | equals= | | X^3+7x^2=x^2+16x | | n=3/4 | | (X^3)+(3x^2)-8x=0 | | y=(3/5*-2)-2/3 | | y=3/5×-2-2/3 | | 9x-7=6-4+5 | | (-12/47)(-47/24)= | | (-12/47)(-47/12)k= | | (16x)^(1/2) | | 5x+(-5+9)=-3 | | 16x+8y=85 | | x^2y-x^2+16y=0 | | (16-2x)(12-2x)=96 | | h=-0.44t^2+2.2t+10 |